VARIATION FORM IN MOZART’S PIANO WORKS - Boglárka Eszter OLÁH (Studia Universitatis Babeş-Bolyai. Musica, 2017)
This study presents the variation form in Wolfgang Amadeus Mozart’s piano works. At first there is a short description of the variation form. From each genre, where the variation form appears in Mozart’s piano works, I chose the most representative example: the “Je suis Lindor“ Variations as an independent variational work, the first movement of the A major piano sonata KV 331 as a variational part of a solo piano work and the second movement of the E flat Major KV 482 piano concerto as a part of a concert. By analysing the works mentioned before I obtained a clear image about Mozart’s harmonical language, form and structure, character and tonalities in his variational piano works.